Pengaruh Motivasi Berprestasi dan Kemandirian Belajar terhadap Prestasi Belajar Matematika Siswa - Ika Sufatihah (JKPM (Jurnal Kajian Pendidikan Matematika), 2018)
The purpose of this study was to determine the impacts of achievement motivation on student’s mathematics learning achievement. To know the impacts of learning independence on student’s mathematics learning achievement. To know the impacts of achievement motivation and learning independence on student’s mathematics learning achievement all together.the methode used in this reseach is survey methode. The numbers of sample are 80 students chosen randomly from all the students of x grade, state SMK in west Jakarta, semester 1 at academic years 2014/2015. Collecting data was conducted by quisionare spread for achievement motivation and learning independence, and report card semester 1 academic years 2014/2015 for student’s mathematics learning achievement. Data analysis used descriptive, statistic classical assumption test, partial correlation coefisient, double correlation coefisient and regression analysis. Sample are 80 students from 111 students. Regression analysis= 71.347+ 0.086X1 + (-0.48)x2, from the equation show that: 1) there are significant impacts of achievement motivation and learning independence on student’s mathematics learning achievement all together. F0 = .1.803 dan Sig. = 0.172 > 0.05, 2) there are significant impacts of achievement motivation on student’s mathematics learning achievement. It is proven by t test= 1.688 and sig= 0.095> 0.05, 3) there are significant impacts of learning independence on student’s mathematics learning achievement. It is proven by t test = -1.028 and sig= 0.307>0.05